ELEMENTAL COMPOSITION OF CONCENTRATED BRINES IN SUBDUCTION ZONES AND THE DEEP CONTINENTAL CRUST - Glassley W.E. (My University, 2001)
It has been well established that fluids played an important part in determining chemical characteristics in many crustal terranes. Studies of fluid inclusions in eclogites have established that brines coexisted with the primary mineral assemblages during their metamorphic crystallization. These brines are currently multiply saturated in halide salts, carbonates, oxides, and sulfides. As a first step in quantitatively bounding the composition of the brines during metamorphism, the equilibrium compositions of the brines at room temperature were computed using the aqueous speciation codes EQ3/6. The results demonstrate that the brines are high density solutions (ca. 1.4 g/cm3) that have ionic strengths of approximately 8 mol, and are approximately 40% dissolved solids, by weight. These are predominately Na- and K-rich brines, with subordinate Ca and Mg. The approximate Na:K:Ca:Mg molar ratios are 4:2:0.5:0.2, but are sensitive to the assumed HCO3− concentrations. Charge balance is primarily maintained by the very high Cl concentrations. These brines bear resemblance to brines analyzed from fluid inclusions in metamorphic rocks reported by Roedder (Roedder, E., 1972. Composition of fluid inclusions. US Geol. Surv. Prof. Paper 440JJ, p. 164). Although these fluids have the potential of acting as significant metasomatic agents in subduction zones and deep crustal environments, their impact will be mineralogically discernible only if the fluid release and movement is channelized.